(untitled) (International Journal of Sustainable Energy and Environmental Research, 2014)
The study empirically examines the effect of subsidies on the consumption of petroleum products in Nigeria for the period of 1970 to 2007. The study employs Augmented-Dickey Fuller (ADF) test for unit root, Engle and Granger (1987) approach for cointegration and Error Correction Model (ECM) for correcting disequilibrium. The ADF test suggests that the variables are mean reverting series after first order difference. The results of the cointegration and ECM confirm that a stable, long-run relationship exists between the demand for petroleum products and their respective determinants: subsidies, real income, prices of the products, prices of substitutes and population. The empirical results show that the elasticity of own and substitutes’ prices are negative, while the own price of diesel, subsidy, real income and population coefficients are positive. Meanwhile, the coefficient of subsidy on gas demand is negative. Hence, the removal of subsidy from petroleum products is not the problem, but the misapplication of the fund meant for the subsidy. This is due to the fact that the subsidy does not reflect in the prices of petroleum products in Nigeria. Therefore, the managers of the economy should ensure that subsidies are better used to achieve economic growth.